(untitled) (Economic and Political Thought, 2023)
The article’s primary goal is to present a thorough study of how the Inflation Reduction Act (IRA) has affected US economic competitiveness and the execution of initiatives to reduce reliance on foreign markets for US business. This analysis evaluates these solutions in light of US technological advantages and critically examines the main business assistance tools for manufacturing and energy technologies provided by the IRA Act.